A theoretical study of electron impact excitation of the lowest autoionizing states of rubidium using a distorted wave method - Fredrick Omboga Oketch (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
In this study, we applied distorted wave method to calculate integral cross sections, differential cross sections, and alignment parameters for electron impact excitation of the lowest autoionizing state of Rb. The projectile electron energy we considered is in the range of near threshold up to high energy region (1 keV). We considered static potential of the initial target state as the initial channel distortion potential and a linear combination of static potentials of initial and final target states as the final channel distortion potential. The wave functions used in this model are the multi-zeta and the double-zeta Hartree-Fock single electron wave functions. In order to perform the numerical calculations, we have modified distorted wave Born approximation 1 (DWBA1) program. In the present study, we have evaluated the exchange amplitudes exactly without any approximation. We have compared our results with other theoretical and experimental results available to us. The present results for integral cross sections are in good agreement with experimental results of Borovik. Our distorted wave results are in much better agreement with the experimental result than does the Dirac B-spline R-matrix results of Borovik. Additionally, our alignment parameter results show a near threshold maximum. Furthermore, from the present differential cross sections results it is observed that when the incident energy increases to 200 eV, the cross sections with or without the effect of exchange coincide nearly at all scattering angles.